Deciphering local complex order by HAADF in a disordered mixed polyanion iron oxide: Sr4Fe2[Fe0.5(SO4)0.25(CO3)0.25]O7.25. Issue 37 (31st August 2018) - Gonano, Bruno; Bréard, Yohann; Pelloquin, Denis; Caignaert, Vincent; Pérez, Olivier; Pautrat, Alain; Bazin, Philippe; Suard, Emmanuelle; Boullay, Philippe
Abstract : Compound Sr4 Fe2.5 O7.25 (SO4 )0.25 (CO3 )0.25 shows a complex local order between polyanions which has been highlighted by means of neutron diffraction and HAADF. Abstract : A layered iron compound involving two divalent polyanions (carbonate and sulfate anions) was synthesized by solid state chemistry in a closed ampule in the form of a ceramic. The Sr4 Fe2 [Fe0.5 (SO4 )0.25 (CO3 )0.25 ]O7.25 compound derives from the third term of the Ruddlesden and Popper family, Sr4 Fe3 O10 . A multiscale approach through transmission electron microscopy (TEM) and powder neutron diffraction (PND) studies shows that SO4 and CO3 groups substitute for the iron polyhedron of the central layer of the perovskite blocks and the absence of long range ordering between sulfate and carbonates and FeO5 groups. Nevertheless, waves disturbing the expected periodicity of the atomic layer are evidenced in HAADF images. An accurate analysis of these images provides a view of the local cationic order correlated with SO4 and CO3 for FeO5 substitution.